The rank abundance distribution of large-bodied vertebrates from Natural Trap Cave, Wyoming. (20th February 2023) - Redman, Cory M.; Moore, Jason R.; Lovelace, David M.; Meachen, Julie A.
Abstract: Natural Trap Cave (NTC) is a well-known fossil locality located in Wyoming that contains a discontinuous record of sediments from the early Sangamonian (∼150 ka) to the present and produces a diverse vertebrate assemblage from 2-9 and 23–47 cal ka BP. This study examines changes in the rank abundance distribution (RAD) of NTC's large-bodied (>8 kg) vertebrates, to assess the stability of the local ecosystem surrounding the cave across the Late Pleistocene-Holocene transition. RADs were generated based on 2208 skeletal elements from four stratigraphic units, collected by Gilbert and Martin from 1974 to 1979. All bones included in this study had: a north-west grid coordinate, a known depth below the sediment surface, were over 20% complete and taxonomically diagnostic. Isotaphonomy was assessed using multinomial regressions of %MAU against multiple taphonomic variables: size, shape, degree of abrasion and weathering, fracture type, percent complete, original bulk density, and surface area to volume ratio. Changes in RADs were analyzed using rank abundance curves (RACs), Wilcoxon Rank Sums test, and kurtosis. RADs were also fit to a suite of standard ecological models (i.e., geometric, log-series, zero-sum multinomial, & log-normal) using maximum likelihood and the Akaike Information Criterion corrected for small sample size (AICc). The four faunal assemblages show little variation in taphonomic biasing, so any changes in the RADs reflects changes in the ecosystem. The four RACs showed little change in their shape or faunal composition and are dominated by a few abundant taxa, representing an ecosystem that experienced perturbations (i.e., a concave RAC and a kurtosis value > 3). The Wilcoxon Rank Sums test found no statistical difference among the RADs from the lower three stratigraphic units. This means that the abundance structure of the large-bodied vertebrates did not change prior to (35.8–25.3 cal ka BP) or during the Last Glacial Maximum (25.3–17.2 cal ka BP) and the local ecosystem surrounding NTC never approached equilibrium. The uppermost stratigraphic unit represented a mixed Late Pleistocene and Early Holocene assemblage, so changes in ecosystem structure from the Last Glacial Maximum to the Holocene (10.5 cal ka BP – present) cannot be evaluated. Unfortunately, the ecological models used in this study provide little insight into the maturity or processes influencing the formation of the local ecosystem surrounding NTC because only three models produced a ΔAICc value between 4.4 and 6.7.